The basic law paradigm in the sociological spotlight: Between ideality and social reality - Dinda Chamelia Sari (Universitas Negeri Yogyakarta, 2025)
This research aims to understand how law works in people's lives by looking at it from a sociological perspective. So far, the law is often regarded as a rule that cannot be contested because it is written in the law. But in reality, the law does not always work as expected. Many cases of injustice occur, especially against weak groups. For this reason, a sociological approach is needed so that the law can be more humane and in accordance with the real conditions in society. This research was conducted with a qualitative method through literature study, namely reading and analyzing relevant books and scientific writings, including the thoughts of progressive legal experts. The results of this research show that the law should not only focus on rules, but should also pay attention to the values of social justice and the culture of the community. One approach that supports this is progressive law, which is law that dares to make breakthroughs for the common good. This research concludes that law in Indonesia needs to be built in a way that is more sensitive to social reality, so that it can truly bring justice, not just certainty. By combining normative and sociological legal approaches, the law will be more easily accepted and implemented by the community.